Migrating to technology integrated classes to promote higher order thinking skills among university students: perspectives from mathematics academicians - Letchumanan, M.; Husain, S. K. S.; Ayub, A. F. M.; Kamaruddin, R.; Zulkifli, N. N. (Universiti Putra Malaysia, 2022)
This study investigates factors that influence the use of information and communication technology (ICT) tools by academicians to promote higher order thinking skills (HOTS) among university mathematics students. The study adapted constructs such as performance expectancy, effort expectancy and facilitating conditions from the Unified Theory of Acceptance and Use of Technology. The study applied descriptive research design and used quantitative and qualitative approach in the form of questionnaire and interview to gather data from 86 academicians from three local public universities in Malaysia. The data were analysed in terms of descriptive analysis and content analysis. The result showed that the technology, instructor, student, learning material, task and organisational factors play important roles in promoting HOTS among students. The study contributed to expanding readers' understanding of the factors that influence the use of ICT tools by academicians to promote HOTS among university students.